Tindak Pidana Pornografi dalam Putusan Pengadilan Negeri Sleman Nomor 220/Pid.Sus/2022/PN Sleman - Mutiara Rizka Azzahra (CV Rewang Rencang, 2025)
ABSTRACTThe development of information technology has given rise to new forms of criminal acts, one of which is the distribution of pornographic content through the internet. This condition creates legal problems due to the overlapping regulations between Law Number 44 of 2008 concerning Pornography and Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE Law) in prosecuting perpetrators.This study assesses the appropriateness of the Public Prosecutor’s decision to indict the defendant under the Pornography Law in Sleman District Court Decision Number 220/Pid.Sus/2022/PN Smn, and analyzes its implications for the principle of legal certainty and the protection of victims.The research method used is normative juridical research with statute, case, and conceptual approaches. The data consist of primary, secondary, and tertiary legal materials, which are analyzed qualitatively.The results show that the application of the Pornography Law can be justified formally since the elements of the article are fulfilled. However, from the perspective of the Lex Specialis Legi Generali principle, the ITE Law is more relevant as it specifically regulates acts committed through electronic media. Relying solely on the Pornography Law creates potential legal uncertainty and provides less optimal protection for victims.In conclusion: (1) formal legal certainty is achieved through the fulfillment of the elements of the Pornography Law, but substantive legal certainty is not fully realized; (2) the ITE Law should serve as the primary legal basis in prosecuting the distribution of pornographic content through digital means, while the Pornography Law should function as a complementary regulation.Keywords: Lex​Specialis​Principle,​Legal​Certainty,​Victim​Protection, Pornography Law, ITE Law, Decision Number 220/Pid.Sus/2022/PN Sleman.